Anatomical Study of the Variations of Sinuatrial and Atrioventricular Nodal Arteries in Human Heart - Verma, Ranjana; Guha, B K; Shrivastava, S K (International Journal of Medical Research and Review, 2014)
Introduction: The conducting system of the heart is supplied mainly by Sinuatrial nodal artery and Atrioventricular nodal artery. Generally, in 60% subjects, Sinuatrial nodal artery arise from Right Coronary Artery and in remaining 40% it arise from Left circumflex branch of Left Coronary Artery. Similarly, the atrioventricular nodal artery arises from Right Coronary Artery in 80% and from Left Coronary Artery in 20% subjects. The aim of the present study is to observe the variation of Sinuatrial & Atrioventricularnodal arteries in human hearts for gathering adequate information study which may be helpful for cardiovascular surgeries. Material and Method: Present study included 50 human hearts. Heart specimens obtained from department of Anatomy of Netaji Subhash Chandra Bose medical College, Jabalpur, India. The course of Sinuatrial nodal and Atrioventricular nodal arteries were traced by micro dissection under water method. Results: In the present study Sinuatrial nodal artery arose from RCA in 52% cases, from LCA in 24% cases and in 24% cases it arose from both RCA & LCA. Likewise, Atrioventricular nodal artery arose from RCA in 88% cases and in 12% cases it arose from LCA. Conclusion: Considering the necessity of Open heart surgeries it becomes necessary to have a deep knowledge of origin and variation of Sinuatrial nodal and Atrioventricular nodal arteries. Knowledge of variation in the blood supply of conducting system may help cardiac surgeons in taking due cautions during various cardiac surgeries, atrial surgical interventions and surgery related to certain valvular disorder and congenital malformation.